Variation patterns of physical property parameters for pipeline transportation of impurity-containing NH3 - Pengbo YIN; Bo WANG; Zhenchao LI; Chaofei NIE; Jiaqing LI; Xiucan JIA; Lin TENG; Lilong JIANG (You-qi chuyun)
ObjectivePipeline transportation is one of the most economical and safest methods for the large-scale transport of ammonia (NH3), which is recognized as a clean energy source. However, during this process, NH3 may become mixed with impurities due to the synthesis process and the transportation environment. These impurities can alter the phase equilibrium characteristics and physical properties of NH3, subsequently affecting transport efficiency and posing potential safety hazards to the pipeline transportation process. MethodsUsing existing experimental data on the physical properties of NH3, a comparative analysis was conducted among commonly used gas equations of states (PR, SRK, and BWRS) and the Helmholtz free energy model (THB). This analysis facilitated the selection of a suitable model for subsequent calculations of the physical properties of impurity-containing NH3. Based on the chosen model, the phase equilibrium characteristics and development patterns of physical properties were explored across binary mixtures of NH3 with varying concentrations of H2, N2, O2, and H2O. ResultsThe calculation results indicated that the PR equation of state exhibited higher precision compared to the other options for the impurity-containing NH3 mixture systems. For example, when examining the density of the NH3+H2O mixture, the average deviation of the calculated values based on the PR equation of state from the experimental values was only 1.2％. Both non-polar and polar impurities were found to influence the bubble point and dew point lines of the NH3 mixture systems, resulting in an expanded gas-liquid two-phase region and a shift at the critical points. The non-polar impurities (H2, N2, and O2) transformed the abrupt increases in density and viscosity of NH3 at the phase transition points into significant declining trends. As a result, these impurities contribute to a more stable flow of pipeline-transported NH3 during phase transitions. This effect was particularly pronounced in systems containing these impurities with lower molecular weights, higher concentrations, and elevated temperatures. However, the effects on density and viscosity were less noticeable for NH3 remaining in the gaseous phase. The non-polar impurities also caused a decrease in the specific heat capacity of NH3 at the phase transition points, with a sudden change occurring at higher pressure levels. This effect became more evident with increasing molecular weights, concentrations, and temperatures of the impurities. The variation trends of NH3 regarding density, viscosity, and specific heat capacity were found to be less affected by the polar impurity of H2O, despite a corresponding increase in these values with rising H2O concentrations. ConclusionThe research results provide guidance on the phase control of pipeline-transported liquid ammonia in the presence of impurities, offering theoretical support for predicting transport characteristics and maintaining a flowable state in pipelines carrying impurity-containing liquid ammonia. Future research is recommended to explore the fundamental thermophysical properties of ammonia, incorporating a wider range of impurities at varying concentrations, and addressing actual impurity-related issues that may arise from the large-scale construction and operation of liquid ammonia pipelines. This will help ensure the stability and safety of the liquid ammonia transportation process.